2014
DOI: 10.4103/0028-3886.128276
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of expression of epidermal growth factor receptor and p53 in meningiomas

Abstract: EGFR expression and Ki67 LI correlated with grade of meningioma P < 0.0001 and P < 0.0001 respectively which were statistically significant whereas p53 expression did not correlate (P - 0.90).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Since normal meninges were EGFR immunonegative, our findings support a general upregulation of this receptor in meningioma tissue in accordance with previous results and other studies (Carroll et al, 1997; Di Carlo et al, 1992; Halper et al, 1999; Horsfall et al, 1989; Huisman et al, 1991; Johnson et al, 1994; Kuratsu et al, 1994; Laurendeau et al, 2009; Lusis, Chicoine & Perry, 2005; Maiuri et al, 2007; Narla et al, 2014; Reubi et al, 1989; Torp et al, 1992). These findings are also supported by studies in which EGFR expression in meningiomas was determined by other techniques such as Northern and western blots, polymerase chain reactions (PCR) and ligand-binding studies (Andersson et al, 2004; Carroll et al, 1997; Guillaudeau et al, 2012; Kurihara et al, 1989; Laurendeau et al, 2009; Torp et al, 1992; Weisman, Raguet & Kelly, 1987).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Since normal meninges were EGFR immunonegative, our findings support a general upregulation of this receptor in meningioma tissue in accordance with previous results and other studies (Carroll et al, 1997; Di Carlo et al, 1992; Halper et al, 1999; Horsfall et al, 1989; Huisman et al, 1991; Johnson et al, 1994; Kuratsu et al, 1994; Laurendeau et al, 2009; Lusis, Chicoine & Perry, 2005; Maiuri et al, 2007; Narla et al, 2014; Reubi et al, 1989; Torp et al, 1992). These findings are also supported by studies in which EGFR expression in meningiomas was determined by other techniques such as Northern and western blots, polymerase chain reactions (PCR) and ligand-binding studies (Andersson et al, 2004; Carroll et al, 1997; Guillaudeau et al, 2012; Kurihara et al, 1989; Laurendeau et al, 2009; Torp et al, 1992; Weisman, Raguet & Kelly, 1987).…”
Section: Discussionsupporting
confidence: 93%
“…In their study, Hilton et al found significantly higher expression of phosphorylated EGFR in tumor tissues compared with non-neoplastic tissues, and high expression of downstream signaling molecules (Hilton et al, 2016). The literature is conflicting concerning EGFR and malignancy, as some have found that high expression is positively related to tumor grade (Caltabiano et al, 2013; Diedrich et al, 1995; Halper et al, 1999) whereas others have found the opposite or no differences (Baxter et al, 2014; Guillaudeau et al, 2012; Jones et al, 1990; Kuratsu et al, 1994; Narla et al, 2014; Wernicke et al, 2010). However, these previous studies have not investigated the activated receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR and the ligands EGF and TGFα have been shown to be overexpressed in human meningiomas (Andersson et al 2004;Baxter et al 2014;Caltabiano et al 2013;Camby et al 1997;Carroll et al 1997;Diedrich et al 1995;Guillaudeau et al 2012;Halper et al 1999;Johnson et al 1994;Kuratsu et al 1994;Laurendeau et al 2009;Lusis et al 2005;Maiuri et al 2007;Narla et al 2014;Reubi et al 1989;Torp et al 1992;Wernicke et al 2010), whereas nonneoplastic meningeal tissue show sparse or no reactivity (Carroll et al 1997;Johnson et al 1994;Torp et al 1992), indicating a potential tumorigenic role of EGFR in these tumors Both membranous and cytoplasmic EGFR immunoreactivity have been described in meningiomas (Guillaudeau et al 2012;Halper et al 1999;Horsfall et al 1989;Johnson et al 1994;Jones et al 1990; Smith et al 2007;Torp et al 1992), however, the prognostic relevance is scarcely described (Guillaudeau et al 2012). The receptor also seems to be activated (phosphorylated) PeerJ reviewing PDF | (2016:10:14229:2:0:NEW 27 Feb 2017)…”
Section: Introductionmentioning
confidence: 99%